DAMPAK PROGRAM KELOMPOK USAHA BERSAMA (KUBE) TERHADAP PENDAPATAN DAN KESEJAHTERAAN MASYARAKAT DI KECAMATAN PALLANGGA KABUPATEN GOWA - Firman Firman; Dirwan Dirwan; Mariah Mariah (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2020)
The purpose of the research is to determine the impact of joint business group (KUBE) program toward community income and wefare in Palangga District of Gowa Regency. This research is a qualitative descriptive research. The information in this research were the people as Palangga Sub-district which were included in KUBE members with total of sample were 9 respondents. Data collection techniquesused were observation, interviews and documentation. The data analysis method used in this research consisted of data reduction data presentation and verification. The results of the research revealed that the joint business group (KUBE) program had a positive impact toward the income and welfare of the people who were members of the joint business group (KUBE).